Comparison Of Measuring Instruments Designed To Electrical Properties Analysis Of Epoxy Resins With Different Fillers - Horák, Luděk (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
Presented thesis is focused on studying electroinsulating epoxy resin-based sealings. It describes the chemical composition, production, properties and measuring methods of basic electric quantities of these materials. The aim of the thesis is to compare several sets of samples of composite epoxy resins with different kinds of micro-ground siliceous sand as a filling. The temperature and frequency dependence of relative permittivity, dissipation factor and volume resistivity are measured for given samples.
Keywords: Epoxy resins; thermosets; electrical insulation materials; dielectric; fillers; polyreaction; electrical properties; diagnostic techniques and measurement; permittivity; dissipation factor; resistivity